1981
DOI: 10.1098/rstb.1981.0059
|View full text |Cite
|
Sign up to set email alerts
|

Phosphofructokinase: structure and control

Abstract: Phosphofructokinase from Bacillus stearothermophilus shows cooperative kinetics with respect to the substrate fructose-6-phosphate (F6P), allosteric activation by ADP, and inhibition by phosphoenolpyruvate. The crystal structure of the active conformation of the enzyme has been solved to 2.4 A resolution, and three ligand-binding sites have been located. Two of these form the active site and bind the substrates F6P and ATP. The third site binds both allosteric activator and inhibitor. The complex of the enzyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
58
1

Year Published

1982
1982
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(59 citation statements)
references
References 12 publications
0
58
1
Order By: Relevance
“…The three-dimensional structure ofunliganded E. coli PFK resembles that of the R state (10), indicating that cooperativity (as well as activation by ADP or GDP) could involve only this R state. Also, the PFKs from E. coli and Bacillus stearothermophilus have similar three-dimensional structures, and both undergo a transition from the R to the T state upon binding PEP (5,6,11), but the two enzymes have different saturations by Fru-6P: extremely cooperative for E. coli PFK (3) and hyperbolic for B. stearothermophilus PFK (12). These results indicate that the cooperativity of PFK does not seem coupled to the transition between the crystallographic R and T states.…”
mentioning
confidence: 99%
“…The three-dimensional structure ofunliganded E. coli PFK resembles that of the R state (10), indicating that cooperativity (as well as activation by ADP or GDP) could involve only this R state. Also, the PFKs from E. coli and Bacillus stearothermophilus have similar three-dimensional structures, and both undergo a transition from the R to the T state upon binding PEP (5,6,11), but the two enzymes have different saturations by Fru-6P: extremely cooperative for E. coli PFK (3) and hyperbolic for B. stearothermophilus PFK (12). These results indicate that the cooperativity of PFK does not seem coupled to the transition between the crystallographic R and T states.…”
mentioning
confidence: 99%
“…Similarly, our results indicate that each protein examined can multimerize, consistent with previous observations. Indeed, each of these molecules has been shown to form homodimers (DEAD box RNA helicase, enolase, RNase Y, and RnpA [4,6,9,15]), trimers (PNPase [22]), tetramers (phosphofructokinase and RNase J1/J2 [7,23]), or combinations of multimer populations (RNase J1 and J2 form homodimers and homotetramers [17]). While the goal of the current study is to genetically evaluate the potential interacting partners of the S. aureus degradosome, it is clear that such work must be bio- As a preliminary means of validating our bacterial two-hybrid analyses, we biochemically confirmed that purified RNase J1 and RNase J2 interact in vitro; both are hypothesized to be essential S. aureus enzymes (5) and, thus, may play major roles in mRNA decay.…”
mentioning
confidence: 99%
“…These transient interactions of protein complexes can cause several effects such as activation/ inactivation of certain proteins, resulting in the formation of a new binding site. 167,168 Kinetics properties of enzymes can be also altered by denaturation during the entrapment process allowing potential change of the protein specificity to its substrate. [169][170][171] Gaining a clear picture of these basics knowledge will definitely lead to a change of object design to increase the protein load, to control the protein release and to retain the protein integrity and efficacy.…”
Section: Protein Encapsulationmentioning
confidence: 99%